2006
DOI: 10.1158/1055-9965.epi-06-0159
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Breast Density in Foreign-Born, U.S. Chinese Women

Abstract: The role of acculturation in the breast cancer risk increase among U.S. Chinese women is unclear. We examined the association between acculturation and breast density in a sample of foreign-born, U.S. Chinese women and examined factors that may explain such an association. Between January 2002 and May 2003, 212 Chinese women were recruited from Philadelphia region screening programs. Cranial-caudal mammographic images were classified into one of four categories ranging from ''entirely fatty'' to ''extremely de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 33 publications
5
33
0
Order By: Relevance
“…Differences in an area-based measure of breast density and level of acculturation by Chinese women in the United States has been found (Tseng et al, 2006). This was only partially explained by risk factors (primarily parity and dairy food consumption).…”
Section: Discussionmentioning
confidence: 98%
“…Differences in an area-based measure of breast density and level of acculturation by Chinese women in the United States has been found (Tseng et al, 2006). This was only partially explained by risk factors (primarily parity and dairy food consumption).…”
Section: Discussionmentioning
confidence: 98%
“…A similar transition has occurred between 1975 and 2005 among Filipino women in Hawaii, where breast cancer incidence rates increased from 44 to 88, and among Native Hawaiian women, where the rates increased from 119 to 148. The transitional period may be especially risky (5969). Incidence rates of breast cancer among Asian-American, Native Hawaiian, and Pacific Islander women increased between 2003 and 2012 as compared to non-Hispanic white women, and the reasons for this increase are thought to be related to changes in reproductive patterns and increased body weight that occur with acculturation after immigration (58).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, especially abdominal adiposity, is a risk factor for postmenopausal breast cancer (22, 23). Studies have shown that other ethnic groups (Japanese, Koreans, Chinese, Hispanics) experienced changes in diet and weight parameters as they migrated to the U.S. and became more acculturated into a Westernized life style (59, 60, 62, 65, 66, 68, 69) and that these changes affected their risk of cancer and other chronic diseases (61, 63, 64, 67). …”
Section: Discussionmentioning
confidence: 99%
“…High-density parenchymal patterns have also been considered a surrogate for mammary gland mass and are strongly associated with breast cancer risk (193,194). Interestingly, data show that among Chinese women who migrated to the United States, the most acculturated have the densest breasts, and that this is not explained by reproductive and lifestyle factors related to density (195). Whereas high-density patterns are a surrogate for the combination of the proportion of the breast occupied by epithelium and stroma (192), their correlation with actual ductal mass is unknown.…”
Section: Prenatal Risk Factors For Breast Cancermentioning
confidence: 99%